Sero—salivary detection of H. pylori immunoglobulins and parasitic infection among healthcare individuals suffering from gastrointestinal disorders with correlation to personal hygiene - Faika Hassanein; Mohamed S. Abdel-Latif; Amany I. Shehata (Gut Pathogens)
Abstract Background Gastrointestinal microbial infections among healthcare individuals (HCIs) are common due to several risk factors, including poor personal hygiene and socio-economic lifestyle. Objectives This is the first cross-sectional study that stratifies HCIs to correlate personal hygiene and socio-economic lifestyle with gastrointestinal microbial infections. Additionally, it compares serum and saliva levels of H. pylori-IgG and IgA to assess the potential of saliva as a non-invasive alternative to serum. Methods Based on Fisher’s formula, 200 HCIs suffering from gastritis—including hospital workers, employees, nursing students, nurses, and doctors—were enrolled. Blood, saliva, and stool samples were collected for microbial infection investigations. Personal hygiene and socio-economic factors were scored based on WHO guidelines. Parasitic infections were identified microscopically, while H. pylori antigen and antibodies were detected via ELISA, with diagnostic significance determined by ROC curve analysis. Results A high prevalence of intestinal microbial infections was observed among HCIs. Blastocystis spp. was the most common pathogen (72%), followed by Cryptosporidium spp. (59.5%). Cases of single, double, and multiple infections were detected. H. pylori antigen was present in 36 (18%) cases, often as a co-infection with intestinal parasites. Infection rates were highest among workers and nurses (100%), followed by employees (97.4%) and nursing students (81.7%), with doctors having the lowest rate (50%). Poor personal hygiene and socio-economic lifestyle were directly linked to increased infection risk. Additionally, H. pylori-IgG was positive in 14 cases and negative in 186 cases, while H. pylori-IgA was positive in 2 cases and negative in 198 cases in both serum and saliva. These findings indicate consistency between serum and saliva levels of H. pylori immunoglobulins. Conclusions Poor personal hygiene and socio-economic lifestyle significantly increase the risk of gastrointestinal microbial infections among HCIs. Salivary immunoglobulins show consistency with serum levels, suggesting saliva as a viable non-invasive alternative for detecting H. pylori infection.